Steroid metabolome in plasma from the umbilical artery, umbilical vein, maternal cubital vein and in amniotic fluid in normal and preterm labor - Hill, Martin; Parízek, Antonín; Kancheva, Radmila; Dusková, Michaela; Velíková, Marta; Kríz, Lubomír; Klímková, Michaela; Pasková, Andrea; Zizka, Zdenek; Matucha, Petr; Meloun, Milan; Stárka, Luboslav (The Journal of steroid biochemistry and molecular biology, 2010)
The boost in placental production of CRH in late pregnancy is specific for human. CRH receptors are expressed in the fetal zone of the fetal adrenal (FZFA). Hence, we evaluated the associations between the steroid metabolome and gestational age (GA). The levels of 69 steroids and steroid polar conjugates such as 3beta-hydroxy-5-ene steroids (3betaOH5S), 3-oxo-4-ene steroids (3O4S), progesterone 5alpha/beta-reduced metabolites, 20alpha-hydroxy-metabolites of C21 steroids, C19 5alpha/beta-reduced metabolites, 7alpha/beta-hydroxy-metabolites of 3betaOH5S, estrogens and 16alpha-hydroxy-metabolites of 3betaOH5S and 3O4S, were measured by GC-MS in plasma from the umbilical artery (UA), umbilical vein (UV), and maternal cubital vein (MV) and in amniotic fluid (AF) in 12 women at normal labor and 38 women at preterm labor due to pathologies unrelated to steroid status. Using multivariate regression, prediction models for GA were completed for the individual body fluids. The conjugated 3betaOH5S (the key products of the FZFA), estrogens, some polar conjugates of progesterone 5alpha/beta-reduced metabolites and some steroid 7alpha/beta- and 16alpha-hydroxy-metabolites showed strong positive correlations with the GA. The predictivity decreased in the following sequence UV (R=0.950), UA (R=0.945), MV (R=0.895), and AF (R=0.891). Although the predictivity of steroids in maternal blood was slightly less effective when compared with the UV and UA, it was the best solution for further practice.
Keywords: Steroids; plodová voda; Corticotropin-Releasing Hormone; Pregnancy; těhotenství; plynová chromatografie s hmotnostně spektrometrickou detekcí; Adult; Obstetric Labor, Premature; venae umbilicales; Case-Control Studies; dospělí; arteriae umbilicales; Gas Chromatography-Mass Spectrometry; předčasná porodní činnost; Amniotic Fluid; lidé; ženské pohlaví; studie případů a kontrol; Humans; hormon uvolňující kortikotropin; Umbilical Arteries; Umbilical Veins; Metabolome; steroidy; metabolom; Female